Obstetric outcome in patients with rheumatic heart disease: experience of a tertiary hospital. - Sharma Koirala, Poonam (Nepalese Heart Journal, 2017)
Background and Aims: Pregnancy in patients with rheumatic heart disease has always been challenging. Haemodynamic changes in pregnancy with diseased heart may cause adverse maternal and fetal outcome. Methods: A prospective study was done in pregnant women with rheumatic heart disease over a period of 2 years from 2015 to 2016 at Tribhuwan University Teaching Hospital, Kathmandu. Baseline data collected at antenatal period were analyzed with obstetric outcomes. Results: A total of 85 women were enrolled in this study. Sixty percent of the women were primigravida. Mitral stenosis was the commonest lesion (69.41%), followed by mitral regurgitation (25.88%) and aortic stenosis (4.71%). Cardiac events were noted in 32 patients out of which 11 developed pulmonary oedema and 6 had new onset of atrial fibrillation. Vaginal delivery (58.82%) was the commonest mode of delivery followed by cesarean section (24.7%). Eighty percent of women remained in NYHA functional class I and II, whereas 20% had deterioration of functional class. There were more maternal and fetal complications in women with NYHA III or IV in comparison to women with NYHA I or II. Low birth weight infants were found in 37.64% of cases. There was one maternal death in a lady with severe mitral stenosis with moderate mitral regurgitation due to congestive heart failure at 34 weeks of gestation. There were 8 fetal and 11 neonatal death Conclusions: Functional cardiac status during pregnancy has a major impact on maternal and fetal outcome. Rheumatic heart disease diagnosed before pregnancy may improve the outcome. Nepalese Heart Journal 2017; 14(2): 31-34